2011
DOI: 10.1080/18811248.2011.9711749
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Elbow Pipe Flow to Develop a Flow-Induced Vibration Evaluation Methodology for Japan Sodium-Cooled Fast Reactor

Abstract: This paper describes the current status of flow-induced vibration evaluation methodology development for primary cooling pipes in the Japan sodium-cooled fast reactor (JSFR), with particular emphasis on recent research and development activities that investigate unsteady elbow pipe flow. Experimental efforts have been made using 1/3-scale and 1/10-scale single-elbow test sections for the hot-leg pipe. The 1/10-scale experiment simulating the hot-leg pipe indicated no effect of pipe scale in comparison with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Most of the reported literature on FIV in pipe bends in large pipes are for nuclear power plant applications. 12 Yamano et al 13 results prove that both pipe size and configuration have effects on MFIV characteristics. The cost and hazard of comprehensive life scale experiments of oil and gas and nuclear power plant pipework could be prohibitive.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Most of the reported literature on FIV in pipe bends in large pipes are for nuclear power plant applications. 12 Yamano et al 13 results prove that both pipe size and configuration have effects on MFIV characteristics. The cost and hazard of comprehensive life scale experiments of oil and gas and nuclear power plant pipework could be prohibitive.…”
Section: Introductionmentioning
confidence: 93%
“…5 Their findings on the relationship between the nondimensional force fluctuation and Weber number compared fairly to the model by Riverin et al 11 and data from Liu et al 3 Most of the reported literature on FIV in pipe bends in large pipes are for nuclear power plant applications. 12 Yamano et al 13 results prove that both pipe size and configuration have effects on MFIV characteristics. The cost and hazard of comprehensive life scale experiments of oil and gas and nuclear power plant pipework could be prohibitive.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…When compared to straight pipes, the main feature of curved pipes is the presence of a secondary motion consisting of a pair of symmetric, counter-rotating vortices. This Prandtl first kind secondary motion increases heat transfer and mixing, for example, effects that are used in many industrial applications, such as nuclear reactor cooling systems, and food processing [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Pipe bends can be used as a part of several mechanical systems, e.g. heat exchangers (Chang, 2003) reciprocating engines (Hellström, 2010) and nuclear reactors (Yamano et al, 2011). Pipe bends are also used in the oil industry, water supply systems, for fluid and material transportation and to change the direction of flow.…”
Section: Introductionmentioning
confidence: 99%